1989
DOI: 10.1007/bf00266374
|View full text |Cite
|
Sign up to set email alerts
|

Long term results of arthrodesis for severe osteoarthritis of the hip in young adults

Abstract: We examined 40 patients (12 men, 28 women) who had undergone hip arthrodesis for severe osteoarthritis more than 15 years previously. Twenty-one cases were due to congenital dislocation of the hip. The age at fusion was mostly between 30 and 39 years. There was no case in which the position of fusion was unsatisfactory. At follow-up, 26 patients had back pain, 9 had pain in the same knee, 2 in the opposite knee and 3 had pain in both knees. Pain in the opposite hip occurred in 5 patients who had slight osteoar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Unfortunately, 32% experienced difficulties with sexual activity, and more than 70% graded their activity as below average for their age group, particularly the female patients. 4,69 Another study also showed positional disabilities, including difficulty kneeling or sitting, difficulty putting on and taking off socks, and difficulty climbing stairs. 63,69 These patients also experienced significant gait changes, with significant limb-length discrepancy.…”
Section: Historical Progression From Arthrodesis To Arthroplasty For mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, 32% experienced difficulties with sexual activity, and more than 70% graded their activity as below average for their age group, particularly the female patients. 4,69 Another study also showed positional disabilities, including difficulty kneeling or sitting, difficulty putting on and taking off socks, and difficulty climbing stairs. 63,69 These patients also experienced significant gait changes, with significant limb-length discrepancy.…”
Section: Historical Progression From Arthrodesis To Arthroplasty For mentioning
confidence: 99%
“…4,69 Another study also showed positional disabilities, including difficulty kneeling or sitting, difficulty putting on and taking off socks, and difficulty climbing stairs. 63,69 These patients also experienced significant gait changes, with significant limb-length discrepancy. 1,29,39 Biomechanical data reported by several authors 11,34,70 also revealed increased loading in the ipsilateral knee and lower lumbar region, which can accelerate degenerative changes in those regions.…”
Section: Historical Progression From Arthrodesis To Arthroplasty For mentioning
confidence: 99%
“…Functional impairment, and pain and degeneration of the neighboring joints are frequent problems associated with a long-term fused hip [12,52,63,64,68,70]. Between 35% Each author certifies that he or she has no commercial associations (eg, consultancies, stock ownership, equity interest, patent/licensing arrangements, etc) that might pose a conflict of interest in connection with the submitted article.…”
Section: Introductionmentioning
confidence: 99%
“…and 60% of patients with fused hips complain of knee pain and between 57% and 65% complain of low back pain [12,68,70]. Many surgeons consider disability resulting from a fused hip, pain in the surrounding joints, malpositioned ankylosis, or painful pseudarthrosis as indications to convert a fused hip to a THA [12, 45, 52, 62-65, 68-70, 72, 74, 77, 78].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence in slightly more than fifty percent of the patients of low back pain and ipsilateral knee pain many years after operation are well known long terms effects of HA [16], [17], [19], [23], [24], [27], [33], [46]–[48]. The main goal was to demonstrate that with this simple, cheap and reliable technique HA is still a very valuable option for painful hip arthritis in countries where THA accessibility is low.…”
Section: Discussionmentioning
confidence: 99%